Synthesis and characterization of mononuclear cadmium(II) and dinuclear uranyl(VI) complexes with vic-dioximes - Canpolat, E; Kaya, M; Bakirdere, EG (Springer, 2005)
In this study, the mononuclear complexes of cadmium(II) and dinuclear complexes of uranyl( VI) with five vic-dioximes have been obtained. Cadmium( II) forms, with ligands, complexes [((LH)-H-x)(Cl)(H2O)(Cd)] with x = 1-5. Mononuclear complexes with a metal: ligand ratio of 1:1 were obtained for cadmium(II) with the ligands, and a chloride ion and a water molecule are also coordinated to the cadmium(II) ions. Uranyl(VI) complexes of these ligands are a dinuclear structure with mu-hydroxo-bridges. Uranyl(VI) forms, with ligands, complexes [((LH)-H-x)(2)(OH)(2)(UO2)(2)] with x = 1-5, which have a 2:2 metal: ligand ratio. The structures of the complexes were identified by elemental analysis, i.r., and H-1-n.m.r. spectra, u.v.-vis. spectroscopy, magnetic susceptibility measurements, conductivity measurements and thermogravimetric analysis (t.g.a.).
Keywords: Transition-Metal-Complexes; Schiff-Base Ligands; Cu(Ii); Ni(Ii); Zn(Ii); Co(Ii); Copper(Ii); Nickel(Ii); Cobalt(Ii); Oxime